Effect of Hydropriming and Redrying on the Germination of Triploid Watermelon Seeds - Rukui Huang; Sutevee Sukprakarn; Thammasak Thongket; Sunanta Juntakool (Agriculture and Natural Resources, 2002)
Two triploid watermelon cultivars ‘Gold Prince’ and ‘Guangxi 5’ were subjected to hydropriming by soaking in deionized water for 2 hrs with aeration following 24 and 48 hrs incubated at saturated relative humidity. Hydropriming had a promotive effect on germination performance in both cultivars but the overall seed germination percentages did not increase in ‘Gold Prince’. Furthermore, hydrated seeds were redried under different conditions to low down the seed moisture content to 6-7 % and the two cultivars responded differently. The highest germination percentages and lowest mean germination time were obtained from medium drying (40%RH, 20°C) for ‘Gold Prince’ and quick drying (20%RH, 20°C) for ‘Guangxi 5’.